The Influence of Digital Literacy and Organisational Climate on Teacher Performance through Job Satisfaction as a Mediating Variable at CHIS School Bali (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to explore how digital literacy and organisational climate influence teacher performance, with job satisfaction as a mediating variable, within the context of CHIS School Bali. Adopting a quantitative approach, the research analyses the relationships among key variables that play a pivotal role in enhancing the quality of education. The study focuses on four essential dimensions: digital literacy, organisational climate, job satisfaction, and teacher performance. The entire teaching staff, from Playgroup to Senior High School, constituted the population, with a sample of 60 respondents selected for the analysis. The findings reveal that teachers’ proficiency in digital technology and a positive, supportive work environment significantly impact their job satisfaction and performance levels. More specifically, all proposed hypotheses in the study were statistically supported: both digital literacy and organisational climate exert direct and indirect effects on teacher performance, with job satisfaction as a significant mediating factor. The study concludes that when teachers possess strong digital literacy skills and operate within a conducive organisational climate, their job satisfaction increases, leading to enhanced performance outcomes. Recommendations include fostering active use of social media among teachers and students for sharing instructional content and school-related information, and organising regular meetings between teachers and school management to discuss issues and collaboratively seek solutions, building trust and promoting teamwork.